1994
DOI: 10.1021/bi00172a027
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Divalent Metal Ion in Sugar Binding, Ring Opening, and Isomerization by D-Xylose Isomerase: Replacement of a Catalytic Metal by an Amino Acid

Abstract: The distinct roles of the two magnesium ions essential to the activity of D-xylose isomerase from Streptomyces olivochromogenes were examined. The enzyme-magnesium complex was isolated, and the stoichiometry of cation binding determined by neutron activation analysis to be 2 mol of magnesium per mole of enzyme. A plot of Mg2+ added versus Mg2+ bound to enzyme is consistent with apparent KD values of < or = 0.5-1.0 mM for one Mg2+ and < or = 2-5 mM for the second. A site-directed mutant of D-xylose isomerase wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
84
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 26 publications
7
84
0
Order By: Relevance
“…A number of XyI structures with the substrate D-glucose or transition state analogues have been determined. 147,[155][156][157][158][159] Despite very strong binding by the inhibitor, which can potentially induce large protein conformational changes, Petsko and co-workers showed that the overall structural difference between the inhibitor complex and the apoenzyme had a very small C α RMS deviation of 0.27 Å, suggesting such a global comparison of structures was insufficient for characterizing active-site interactions. 147,156 Two structures are compared in the present discussion, the D-glucose complex (1XYB) determined by Whitlow et al 159 and the inhibitor complex (2GYI) determined by Allen et al, 147,156 which leads to a small difference in the proposed coordination sphere to the Mg2 ion (i.e., the second Mg ion cofactor), which is a "mobile" ion during the reaction (Scheme 3).…”
Section: Modeling the Michaelis Complex As The Initial Condition For mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of XyI structures with the substrate D-glucose or transition state analogues have been determined. 147,[155][156][157][158][159] Despite very strong binding by the inhibitor, which can potentially induce large protein conformational changes, Petsko and co-workers showed that the overall structural difference between the inhibitor complex and the apoenzyme had a very small C α RMS deviation of 0.27 Å, suggesting such a global comparison of structures was insufficient for characterizing active-site interactions. 147,156 Two structures are compared in the present discussion, the D-glucose complex (1XYB) determined by Whitlow et al 159 and the inhibitor complex (2GYI) determined by Allen et al, 147,156 which leads to a small difference in the proposed coordination sphere to the Mg2 ion (i.e., the second Mg ion cofactor), which is a "mobile" ion during the reaction (Scheme 3).…”
Section: Modeling the Michaelis Complex As The Initial Condition For mentioning
confidence: 99%
“…159 An important feature of the active site of XyI is a combination of two divalent (Mg 2+ , Co 2+ , Mn 2+ ) ions bridged by an aspartate residue; 250 a growing number of enzymes are now known to share this structural motif. 155,156 The overall enzymatic process is rather complex, involving the opening of the pyranose sugar ring, isomerization by a hydride transfer mechanism, and reclosing to form the cyclic sugar product. 159 X-ray structures have captured a number of intermediate configurations using various substrate and transition state analogue inhibitors.…”
Section: Enzyme and Substrate Conformational Dynamicsmentioning
confidence: 99%
“…203 Allen, K. N., Lavie, A., Glasfeld, A., Tanada, T. N., Gerrity, D. P., Carlson, S. C., Farber, G. K., Petsko, G. A. and Ringe, D. (1994) Baneijee, R., Das, K., Ravishankar, R., Suguna, K., Surolia, A. and Vijayan, M. (1996) Conformation , Proteins: Struct., Funct., Genet., 12,[203][204][205][206][207][208][209][210][211][212][213][214][215][216][217][218][219][220][221][222] Goldstein, I. J., Reichert, C. M. and Misaki, A. (1974) Stidy of Concanavalin A: The Proton of Asp28, J. Chem.…”
mentioning
confidence: 99%
“…The only other direct sugar -metal interaction known is xylose isomerase in which the sugar ligates two Mg^^ ions Lavie et al, 1994). (Naismith et al, 1994;Allen et al, 1994). (Bourne et a l, 1994), pea lectin (Rini et a l, 1993), WGA (Wright, 1992), MBP (Weis et a l, 1992) and the bluebell lectin (SCA) (http://plab.ku.dk/tcbh/Lectinsl2AVright/paper.htm).…”
mentioning
confidence: 99%
“…Although they share only 20 to 30% amino acid sequence identity with group I XIs, the active-site residues in group I and group II enzymes are highly conserved ( Table 1). The structures of monomeric, homodimeric, and homotetrameric XIs from a number of microbial sources including Streptomyces (5-7), Actinoplanes (1,21,29,36), Arthrobacter (37), Bacillus (28), and Thermus (9) were solved by X-ray crystallography. A structural feature of monomeric XIs is that they consist of an (␣/␤) 8 barrel having an active site and a C-terminal loop region.…”
mentioning
confidence: 99%